Biomarkers predicting chemotherapy response in head and neck squamous cell carcinoma: a review. Issue 11 (2nd October 2015) - Cosway, B; Paleri, V; Wilson, J
Abstract: Background: Biomarkers are increasingly being used in many cancers to select patients for oncological treatment paradigms based on their inherent genetic properties. However, in head and neck cancers, there are no personalised therapies available outside the context of a clinical trial. A number of studies suggest there are intrinsic tumour properties of head and neck cancers that affect their response to chemotherapeutic agents. This paper aimed to review their evidence base. Method: A narrative review was conducted following a search of the PubMed database. Results and conclusion: The review identified a number of biomarkers predicting response to chemotherapy in head and neck cancers. The paper discusses these in detail, and explores where future research could be directed in order to deliver personalised therapies for patients with head and neck cancers.